Theoretical conceptions of transnational solidarity in working relations - Ilana Nussbaum Bitran; Irene Dingeldey; Franziska Laudenbach (Institut Arbeit und Wirtschaft (IAW), Universität Bremen und Arbeitnehmerkammer Bremen, 2022)
Solidarity is probably one of the most undeniable concepts of the social sciences as it is present in every group formation being this a country, a family or a trade union. But globalization has questioned the core of traditional solidarity and has challenged us to find new forms of solidarity that go beyond the borders of nation-states when we focus on the transnational or international level. Being once based on the identity and homogeneity of a group, solidarity must now transcend one specific group with a clear identity, clearly defined borders, constant and close interactions and settled stabilization mechanisms, the four prerequisites Engler (2016) found to be at its basis. Globalization brings two issues into play that break with these four prerequisites. On the one hand, it opens up the possibility to constitute groups beyond a specific geographical place and to grasp global problems such as climate change within transnational groups. On the other hand, globalization reinforces the idea of individualization and a decline of collectively shared identity which threads the classical idea of solidarity. In this paper we look for an enlarged concept of solidarity that can be grasped in different "places" in transnational working relations, taking the European Union as an example.
Keywords: 330